Qualitative Differences in the N-Acetyl-D-galactosaminyltransferases Produced by Human A(1) and A(2) Genes - Schachter, H. (1973)
This study describes the kinetic properties of N-acetyl-D-galactosaminyltransferase in serum from subjects with blood groups A(1) and A(2). When the A(1) and A(2) enzymes were compared, with lacto-N-fucopentaose I and 2′-fucosyllactose as acceptors, the enzymes differed in their cation requirements, pH optima, and K(m) values. The two acceptors competed for the same transferase. Mixing experiments showed that the lower activity of the A(2) enzyme could not be attributed to a modifier or inhibitor in serum. It was concluded that the A(1) and A(2) enzymes differ qualitatively.